KOMITE AUDIT SEBAGAI PEMODERASI PENGARUH TAX MINIMIZATION TERHADAP TRANSFER PRICING (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - ayu hartina (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the effect of the tax minimization on transfer pricing with audit committee as a moderating variable. This research used secondary data analysis of financial statements or annual reports of companies consumer goods industry sectors listed on the Indonesia Stock Exchange in 2013-2016. By using purposive sampling method, the total amount of samples obtained in this research were 52 from 13 companies. Data testing method used is linear regression analysis and moderet regresion analysis (MRA). The results of this research show that tax minimization has negative significant effect on transfer pricing with significance level of 0,010. Audit committee not able to weaken the relationship between tax minimization to the transfer pricing with a significance level of 0.162.